Isolated superior mesenteric artery dissection presenting as abdominal pain in a patient with ureteral carcinoma: a case report and literature review - Jia Zheng; Lei Yang; Lianrui Guo (Frontiers in Surgery, 2026)
Isolated superior mesenteric artery dissection (ISMAD) is a rare vascular surgical disease. Its symptoms have no obvious specificity, and it is easy to be misdiagnosed or missed. This paper reports a patient with peritoneal metastasis who was eventually diagnosed with ISMAD presenting with abdominal pain, highlighting the diagnostic challenge and the importance of considering vascular emergencies in oncology patients.